Evaluating Corporate Social Responsibility Reporting Practices in the Sultanate of Oman (2016 to 2018) - Al-Maauli, Sultan Said (Journal of Economic, Administrative and Legal Sciences, 2023)
This study evaluates corporate social responsibility (CSR) reporting practices in the Sultanate of Oman by investigating how stakeholders perceive CSR reporting and practices in different sectors. Moreover, it examines if there is a difference in CSR reporting practices across different sectors over three years, from 2016 to 2018 inclusive. A quantitative multi-method is used in this study to address the objectives and the questions of this research. Overall, the analysis shows that the level of CSR reporting in Oman is moderate in terms of both the stakeholders’ views and the annual reports of the companies. Furthermore, both the stakeholders’ views and the report analysis show a match in the results. Therefore, this result supports the stakeholder theory, which states that companies should make decisions that meet the interests of stakeholders, which includes economic, environmental and social dimensions. Finally, the researcher has two recommendations based on these study findings. Firstly, Oman needs legislation on CSR since there is no legislation to date that defines organizing CSR in Oman. Secondly, Oman needs to give greater attention to spreading awareness to all stakeholders of their power in many corporate activities.
Keywords: Corporate Social Responsibility (CSR); Sultanate of Oman; Stakeholders